Uluslararası borçluluğun evrimi ve IMF - Cinemre, Cihan (My University, 2005)
Name and Surname: Cihan Cinemre Field: Economics Programme: Development Economics and Economic Growth Supervisor: Assistant Proffessor Mehmet Şişman Degree Awarded and Date: Master - January 2005 World System, Capital Accumulation, IMF, World Bank, Money Capital, Foreign Ivestment, Deptness, Imperialism, Uneven Development, Unequal Exchange

THE EVALUATION OF INTERNATIONAL DEPTNESS AND IMF This research's aim is to show the links between the debt crisis, which took place in a series of nations in different historical conditions, and the structure of capital accumulation in that particular time with a historical materialistic method. Therefore the evolution of the world system and capital accumulation is studied since the mid 19th century when the rapid transformation of capitalist system began. A clear understanding of this transformation and the structure was important to understand how the concept of underdevelopment came out, reproduced, deepened and extended. The reasons and outcomes of each particular debt crisis is studied and compared with each other. Another important part of the research is the evolution of relations between money capital and productive capital in accordance with the structure of capital accumulation. This changing relation and partial autonomy of money capital was a major cause for the enormous increase in the supply of credits beginning with 1970s. The differentiation in the relations between IMF and World Bank and in the duties and aims of these two organizations is studied partially. Soyadı:Cihan Cinemre sat Kalkınma İktisadı ve İktisadi Büyüme Yrd. Doç. Dr. Mehmet Şişman Tez Türü ve Tarihi: Yüksek Lisans - Ocak 2005 nya Sistemi, Sermaye Birikimi, Yabancı Yatırım, Sermaye, Borçluluk, IMF, Dünya Bankası, Emperyalizm, Eşit Olmayan Gelişme, Eşit Olmayan Değişim ÖZET ULUSLARARASI BORÇLULUĞUN EVRİMİ ve IMF Bu çalışmanın amacı, farklı tarihsel koşullarda bir dizi devletin yaşadığı borç krizleri arasındaki bağlantıları göstermek ve o döneme özgü sermaye birikim yapısını tarihsel materyalistik yöntemle incelemektir. Bu nedenle kapitalist sistemde hızlı dönüşümlerin başladığı on dokuzuncu yüzyıl ortasından başlayarak dünya sisteminin evrimi ve sermaye birikimi incelenmişir. Söz konusu dönüşümü ve yapıyı anlamak azgelişmişlğin nasıl doğduğunu, nasıl yeniden üretildiğini, derinleştiğini ve yayıldığını anlamak bakımından önemlidir. Belirli dönemdeki borç krizlerinin her birinin nedenleri ve sonuçları incelenmiş ve birbirleriyle karşılaştırılmıştır. Çalışmanın önemli bir bölümünde para sermaye ile üretken sermaye arasındaki ilişkilerin evrimi sermaye birikimi yapısı içerisinde incelenmiştir. Bu değişen ilişki ve para sermayenin kısmi özerkliği 1970 lerde başlayan kredi arzında devasa boyutlara ulaşan artışın en önemli nedenlerindendir. IMF ve Dünya Bankası arasındaki ilişkilerde, dolayısıyla bu iki kuruluşun sorumlulukları ve amaçlarındaki farklılaşma da kısmen incelenmiştir.
Keywords: Borçlar, Dış; Para Politikası